The effect of nutrition labels on lunch buffet consumption: a real-life experiment - Junkkari, Terhi (Emerald Publishing, 2025)
Purpose: This study aims to increase knowledge of the ability of nutrition labels to guide consumer choices in real-life environments. Design/methodology/approach: Food consumption and plate waste data were collected from two self-service restaurants (SSR) with different customer groups over six observation days: three control and three intervention (with nutrition labelling) periods. Study Group 1 consisted of vocational school students, mostly late adolescents (N = 1,710), and Group 2 consisted of spa hotel customers, mostly elderly (N = 1,807). In the experimental restaurants, the same food was served to the buffets during the control and intervention periods. Findings: The nutrition label in the lunch buffet guides customers to eat fewer main foods and salads and to select healthier choices. Increased consumption of taste enhancers (salt and ketchup) was observed in the study restaurants after nutritional labelling. Nutrition labelling was associated with a reduction in plate waste among the elderly, whereas the opposite was observed among adolescents. Originality/value: The results provide public policymakers and marketers with a better understanding of the effects of nutrition labelling on consumer behaviour. Future studies should further evaluate the effects of nutrition labelling on the overall quality of customer diets and the complex environmental, social, and psychological factors affecting food choices and plate waste accumulation in various study groups. © 2023, Terhi Junkkari, Maija Kantola, Leena Arjanne, Harri Luomala and Anu Hopia.